2003
DOI: 10.1097/00004728-200303000-00026
|View full text |Cite
|
Sign up to set email alerts
|

Rhombencephalosynapsis and a Chiari II Malformation

Abstract: Rhombencephalosynapsis is an anomaly of the hindbrain characteristically presenting with cerebellar fusion and absence of cerebellar vermis on magnetic resonance imaging. Its association with spinal anomalies has not been reported previously. We report a unique case, a 22-year-old man with cerebellar fusion associated with a cervicothoracic meningomyelocele, diastematomyelia, tethering of the spinal cord, and dorsal dermal sinuses. In addition, cerebellar tonsillar herniation and tectal beaking similar to that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…At last, we identiWed associated neural tube defects in three cases. Neural tube defects have never been previously reported in fetuses, and only in one adult and two pediatric cases, consisting of RS and cervicothoracic or lumbosacral myelomeningocele [40,46], but not of encephalocele as in our three fetuses.…”
Section: Neuropathological Descriptionsmentioning
confidence: 43%
See 1 more Smart Citation
“…At last, we identiWed associated neural tube defects in three cases. Neural tube defects have never been previously reported in fetuses, and only in one adult and two pediatric cases, consisting of RS and cervicothoracic or lumbosacral myelomeningocele [40,46], but not of encephalocele as in our three fetuses.…”
Section: Neuropathological Descriptionsmentioning
confidence: 43%
“…Other features have also been described, such as malrotated hippocampi, hypoplastic chiasm, fused cerebral peduncles and thalami [2,9,32,34,54], parietal and temporo-parietal cortical dysplasia [32,33], and schizencephalic cleft [33]. Using MRI, associated Dandy-Walker malformation has been observed in four fetuses [36,45] and Chiari I or II malformations have also been reported in two children [46,54], but these malformations were not identiWed using prenatal US or MRI in our cases.…”
Section: Clinical and Mri Diagnosismentioning
confidence: 59%
“…RES has been reported previously in association with Chiari II malformations [Sener and Dzelzite 2003; Wan et al, 2005]; however, it also has been suggested that a small posterior fossa and compression of the cerebellar hemispheres can mimic the appearance of RES [Guntur Ramkumar et al, 2010]. Therefore, we cannot dismiss the possibility that the RES diagnosed in two individuals with Chiari II malformations in this study is not a real observation.…”
Section: Discussionmentioning
confidence: 55%
“…We wonder if the cerebellar herniation in previously reported similar cases [4, 10] was vermian rather than tonsillar. We also wonder if the cases like these represent another description of abnormality as happens in Chiari type II malformation, rather than a new abnormality of hindbrain and spine as has been suggested [10]. This raises an important question of whether PRECS can be diagnosed with Chiari type II malformation in presence of cerebellar vermian herniation (Figs.…”
Section: Discussionmentioning
confidence: 93%
“…The association of Chiari type II malformation and RECS has been suggested before [10] and their coexistence has been thought of as a "new" abnormality of hindbrain and spine [10]. It is not clear if there is any significant common ground for these abnormalities with apparently different embryogenesis.…”
Section: Discussionmentioning
confidence: 99%